Simplify the following expression:
5 + 6 + 2 7 + 3 8 + 4 9 + 5 1 0 + 6 1 1 + 7 . . .
The pattern here is that the coefficients in front of the square root is the sequence 1,2,3..., Pattern(n) = n, starting at n = 1
The terms being added to the square roots are 5,6... Pattern(n) = 4 + n, starting at n = 1
================================================================
Solution technique can be found: http://vixra.org/pdf/1310.0177v1.pdf
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
In case you're too lazy to read the pdf:
The principle is as follows:
( x + n ) 2 = x 2 + 2 x n + n 2
( x + n ) 2 = x 2 + n x + n ( x + n )
( x + n ) 2 = x 2 + n x − n e + n ( x + n + e )
( x + n ) 2 = x 2 + n ( x − e ) + n ( x + ( n + e ) )
x + n = x 2 + n ( x − e ) + n ( x + ( n + e ) )
From here it is easy to show then that for any value e of our choice we can make the substitution
x + n = x 2 + n ( x − e ) + n ( x + n = x 2 + ( n + e ) ( x − e ) + ( n + e ) ( x + ( n + 2 e ) ) )
Now we repeat this substitution indefinitely to get an infinitely nested expression.
The solution then requires us to notice that from the problem it is clear that
n = 1
Furthermore it is clear that e = 1
And therefore
x^2 + x - 1 = 5
Tells us that x = 2 is a viable candidate and therefore the solution is
(2 + 1) = 3